Propuesta de mejora de un sistema de distribución de soluciones nutritivas para la fertiirrigación para la producción de forraje verde hidropónico de cebada (Hordeum vulgare) - Villacis Guevara, Linikeer Armando (2025)
This research work takes place on the campus of the Technical University of Ambato located in Querochaca, in the province of Tungurahua, and is focused on the proposal to improve a nutrient solution distribution system for the production of hydroponic green fodder from barley (Hordeum vulgare). The need to optimize the process of mixing nutrient solutions prompted this proposal from a technical and functional approach, oriented to the design of efficient and sustainable systems. The initial analysis included a study of the water and nutritional conditions required for this type of crop, as well as an exhaustive evaluation of the deficiencies of the current system. Among the problems found, the lack of homogeneity in the mixture and nutrients and the irregularity in the distribution stand out, factors that affect the final quality of the crop. In response to these limitations, a manual mixer (low fidelity prototype) operated by crank was designed and implemented, which was generated under principles of industrial design, seeking functionality. This mechanism generates a more efficient mixture of nutrient solutions, adapts significantly to the needs of the operator and reduces the physical effort required. The result is an improvement in the uniformity of the mixture (in terms of biomass). In addition, proposals for improvement of the nutrient solution distribution system were presented, which were developed and explained theoretically. These include technical recommendations that allow optimizing the system components, such as emitters, tanks and filtration systems, with the aim of ensuring greater efficiency in fertigation and better system performance. The study concludes that the solution generated is an advance in terms of agricultural efficiency and sustainability, which allows the development of practical and replicable tools for small and medium producers. This project provides an opening to learn about the benefits of Industrial Design when incorporated into the agricultural sector, to address specific problems and propose useful and accessible solutions for the target market.